Myrcia auriculata (Myrtaceae), a new species from the Brazilian Atlantic Forest - Fernandes, Thiago; Sobral, Marcos; Santos, Matheus Fortes; Braga, João Marcelo Alvarenga (Phytotaxa, 2019)
Myrcia auriculata, a new species from the Atlantic rainforest of Rio de Janeiro State, southeastern Brazil, is described and illustrated. The new species is morphologically congruent with Myrcia sect. Sympodiomyrcia and is apparently related to M. truncata, differing in its auriculate leaf base, shorter inflorescences and four calyx lobes. Additionally, a distribution map and conservation assessments based on IUCN criteria are provided.